Ucinnost kyseliny fosfonomravencí na herpetická onemocnĕní - Smejkal, F; Otová, B; Zikán, V; Roubínek, F (Ceskoslovenska farmacie, 1992)
The antiviral efficacy of phosphonoformic acid (PFA) was examined on tissue cultures of the human embryonal lungs against the viruses herpes simplex type 1 and 2, herpes zoster, and the human cytomegalovirus using the method of the inhibition of the cytopathic effect and against herpes simplex type 1 and 2 on the tissue cultures of Vero cells using the methods of the inhibition of plaque formation. PFA was demonstrated to inhibit the reproduction of the viruses under study in both tests on tissue cultures. In persistence studies, the cytomegalovirus was not isolated back from the cells of the human embryonal lungs, which gave evidence of its greater sensitivity to PFA. In in vivo experiments, PFA in the form of a 3% ointment suppressed herpetic dermatitis on the guinea-pig skin, when treatment started 6, 24 and 48 hours after infection. In a preliminary experiment on rabbit corneas, an ointment with 3% PFA inhibited herpetic keratoconjunctivitis in time intervals of 1 and 3 hours after infection.
Keywords: morčata; Antiviral Agents; králíci; Herpesviridae; herpetické infekce; Foscarnet; Animals; Herpesviridae Infections; Phosphonoacetic Acid; antivirové látky; zvířata; Rabbits; kyselina fosfonoctová; foskarnet; Guinea Pigs